Tumor Fibroblast Growth Factor Receptor 4 Level Predicts the Efficacy of Lenvatinib in Patients With Advanced Hepatocellular Carcinoma. Issue 5 (22nd May 2020) - Yamauchi, Masami; Ono, Atsushi; Ishikawa, Akira; Kodama, Kenichiro; Uchikawa, Shinsuke; Hatooka, Haruna; Zhang, Peiyi; Teraoka, Yuji; Morio, Kei; Fujino, Hatsue; Nakahara, Takashi; Murakami, Eisuke; et al.
Abstract : OBJECTIVES: Biomarkers for optimizing the outcome of treatment with lenvatinib in patients with advanced hepatocellular carcinoma remain to be established despite intensive and comprehensive genomic research. Lenvatinib is characterized by its prominent inhibitory potency for fibroblast growth factor receptor (FGFR) 4 compared with earlier tyrosine kinase inhibitors. Thus, in this study, we focused on simplified quantification of FGFR4 in tumors as a potential predictive indicator. METHODS: According to The Cancer Genome Atlas data set curation, FGFR4 messenger RNA is broadly overexpressed in hepatocellular carcinoma in the absence of gene alteration. Gene set enrichment analysis revealed that the aggressiveness of the tumor was closely related to the FGFR4 level. To confirm the relationship between the benefits of lenvatinib and tumor addiction to the FGFR4 pathway, we analyzed protein levels in tumors and peripheral blood obtained from 57 prospectively registered patients treated with lenvatinib. RESULTS: Positive immunohistochemistry (>10% of tumor cells) for FGFR4 in biopsy samples before treatment was associated with a longer progression-free survival (2.5 vs 5.5 months, P = 0.01) and a favorable objective response rate (31% vs 81%, P = 0.006). By contrast, the concentration of soluble FGFR4 in peripheral blood as measured by an enzyme-linked immunosorbent assay was not associated with survival outcomes, because its fluctuations reflect hepatic fibrosis. Additional RNA sequencing analysis using archival surgical specimens (n = 90) suggested that alternative RNA splicing of FGFR4 in cancer may also explain this discrepancy. DISCUSSION: The tumor FGFR4 level was an independent predictor of response to lenvatinib.